2011
DOI: 10.1371/journal.pone.0022360
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Inflammation in Renal Patients and Healthy Subjects

Abstract: The first goal of this study was to measure the oxidative stress (OS) and relate it to lipoprotein variables in 35 renal patients before dialysis (CKD), 37 on hemodialysis (HD) and 63 healthy subjects. The method for OS was based on the ratio of cholesteryl esters (CE) containing C18/C16 fatty acids (R2) measured by gas chromatography (GC) which is a simple, direct, rapid and reliable procedure. The second goal was to investigate and identify a triacylglycerol peak on GC, referred to as TG48 (48 represents the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
1
12
0
4
Order By: Relevance
“…The results of the presented studies and those by of other laboratories have already shown that TG-rich apoB-containing apoCIII lipoproteins are linked to inflammation [1,2,[12][13][14], and that oxidation is not always proatherogenic [7,15]. Moderate oxidation that encompasses in vivo conditions destabilizes VLDL and promotes the fission of HDL-size particles.…”
Section: Discussionsupporting
confidence: 54%
“…The results of the presented studies and those by of other laboratories have already shown that TG-rich apoB-containing apoCIII lipoproteins are linked to inflammation [1,2,[12][13][14], and that oxidation is not always proatherogenic [7,15]. Moderate oxidation that encompasses in vivo conditions destabilizes VLDL and promotes the fission of HDL-size particles.…”
Section: Discussionsupporting
confidence: 54%
“…Whereas some reported deceased levels of AGEs when HDF was applied [39,41], others demonstrated no effect [34]. Until now, the effect of HDF on novel inflammatory biomarkers like PTX3, TG48 [48], TWEAK [49] or TRAIL [50] waits for further studies.…”
Section: Effects Of Hdf On Uremic Inflammationmentioning
confidence: 99%
“…Dialysis CKD patients are reportedly characterized by higher levels of oxidative and inflammation than healthy subjects (11,32–34). Oxidative stress and inflammation are correlated strongly with tryglycerides, VLDL‐C, apoC‐III and apoC‐III bound to apoB‐containing lipoproteins, but not with either TC or LDL‐C (35).…”
Section: Mechanisms Involved In the Therapeutic Effects Of Ldl Apherementioning
confidence: 99%